Decay of Singular Values of Power Series Kernels on the Sphere. (2nd April 2016) - Azevedo, D.; Menegatto, V. A.
ABSTRACT: In this article, we provide decay rates for singular values of compact integral operators generated by power series kernels on either the unit sphere or the closed unit ball in ℝ m  + 1, m  ≥ 1 under decay assumptions on the coefficients in the expansion of the kernel. The results are illustrated in concrete examples, including an integral operator generated by a Gaussian kernel on the sphere.